Is Face and Mask Touching a Real Struggle During the COVID-19 Pandemic? A Prospective Study Among Medical Students - Stefaniak, Aleksandra A.; Krajewski, Piotr K.; Białynicki-Birula, Rafał; Nowicka, Danuta; Szepietowski, Jacek C. (Frontiers in Medicine, 2021)
There is limited data in the literature on the frequency of face and mask-touching behavior as a potential vector for the self-inoculation and transmission of the novel coronavirus. In this prospective study, we assessed the facial touching behaviour of 204 medical students. 134 subjects (65.68%) during the 15 minutes observation at least once touched the area of the mask (38.23%), eyes (38.23%) or other parts of the facial zone (49.02%). The mean number of touches was 11.98±16.33 per hour. The results of our study reveal that there is no significant association between mask-wearing and the gender, however, there might be a tendency for people with eyeglasses to touch the area near the eyes more often.